Evolutionarily conserved mechanisms regulating stress-induced neutrophil redistribution in fish - Klak, Katarzyna; Maciuszek, Magdalena; Pijanowski, Lukasz; Marcinkowska, Magdalena; Homa, Joanna; Verburg-van Kemenade, B. M. Lidy; Rakus, Krzysztof; Chadzinska, Magdalena (Frontiers in Immunology, 2024)
Stress may pose a serious challenge to immune homeostasis. Stress however also may prepare the immune system for challenges such as wounding or infection, which are likely to happen during a fight or flight stress response. In common carp (Cyprinus carpio L.) we studied the stress-induced redistribution of neutrophils into circulation, and the expression of genes encoding CXC chemokines known to be involved in the regulation of neutrophil retention (CXCL12) and redistribution (CXCL8), and their receptors (CXCR4 and CXCR1-2, respectively) in blood leukocytes and in the fish hematopoietic organthe head kidney. The potential involvement of CXC receptors and stress hormone receptors in stress-induced neutrophil redistribution was determined by an in vivo study with selective CXCR inhibitors and antagonists of the receptors involved in stress regulation: glucocorticoid/mineralocorticoid receptors (GRs/MRs), adrenergic receptors (ADRs) and the melanocortin 2 receptor (MC2R). The stress-induced increase of blood neutrophils was accompanied by a neutrophil decrease in the hematopoietic organs. This increase was cortisolinduced and GR-dependent. Moreover, stress upregulated the expression of genes encoding CXCL12 and CXCL8 chemokines, their receptors, and the receptor for granulocytes colony-stimulation factor (GCSFR) and matrix metalloproteinase 9 (MMP9. Blocking of the CXCR4 and CXCR1 and 2 receptors with selective inhibitors inhibited the stress-induced neutrophil redistribution and affected the expression of genes encoding CXC chemokines and CXCRs as well as GCSFR and MMP9. Our data demonstrate that acute stress leads to the mobilization of the immune system, characterized by neutrophilia. CXC chemokines and CXC receptors are involved in this stress-induced redistribution of neutrophils from the hematopoietic tissue into the peripheral blood. This phenomenon is directly regulated by interactions between cortisol and the GR/MR. Considering the pivotal importance of neutrophilic granulocytes in the first line of defense, this knowledge is important for aquaculture, but will also contribute to the mechanisms involved in the stress-induced perturbation in neutrophil redistribution as often observed in clinical practice.